Who will be fed in the 21st century? challenges for science and policy - Wiebe, Keith D.; Ballenger, Nicole; Pinstrup-Andersen, Per (International Food Policy Research Institute, 2001)
Global food production has more than doubled over the past 40 years, growing faster than population, and will likely keep pace in the 21st century. Yet today one-eighth of the world's people lack secure access to the food they need to live active and healthy lives. This volume describes how together innovative technologies and sound policies can help close the global food gap -- the gap between demand for and supply of food. Although markets will continue to supply sufficient food to those with money to spend, getting food to the poor will require that government policies and investments supplement the operation of markets in three critical areas: protecting the natural resources on which agriculture depends; focusing the benefits of agricultural research, including biotechnology, on the needs of small farmers in developing countries; and ensuring that access to food, resources, and income-generating opportunities is equitable and secure. Contributors to this book show how soil degradation, biotechnology, and other resources and technologies might affect the future supply of food, as well as how poverty, conflict, and gender roles might affect demand. They also consider the roles that institutions must play in meeting the challenge of global hunger. Finally, they outline the policy priorities required to achieve a food-secure world in the 21st century.